PENGARUH RASIO LIKUIDITAS, SOLVABILITAS, AKTIVITAS, DAN TINGKAT INFLASI TERHADAP KINERJA KEUANGAN PADA PDAM KOTA SURAKARTA - Yuliana - (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
Purpose of this research to analyze the effect of liquidity ratio, solvability ratio, activity ratio and inflation rate on financial performances. Design research is case study at PDAM Surakarta. The type of data used quantitative and qualitative data. Source of data used primary data and secondary data. The technique of collecting data used documentation. The data analysis technique used financial ratios and multiple regression. The results showed that liqudity ratios has significant effect on financial performance. Solvability ratio has significant effect on financial performance. Activity ratio did not significant effect on financial performance. Inflation has significant effect on financial performance. Financial ratios rate PDAM Surakarta in years 2008 – 2013 are not good. Liquidity ratio, solvability ratio, activity ratio and inflation effect on financial performance simultaniously Keywords: liquidity, solvability, activity, inflation and financial performance.